Using focus groups to explore caregiver transitions and needs after placement of family members living with dementia in 24-hour care homes. (1st February 2020) - Cottrell, L.; Duggleby, W.; Ploeg, J.; McAiney, C.; Peacock, S.; Ghosh, S.; Holroyd-Leduc, J. M.; Nekolaichuk, C.; Forbes, D.; Paragg, J.; Swindle, J.
Abstract: Objectives : Family caregivers (defined broadly as family and friends) of persons with dementia are challenged to cope with myriad stressors and changes that occur along the dementia trajectory. The purpose of this study was to explore the transitions experienced by caregivers of persons with dementia after their relative relocated to a 24-hour care home. Method : Qualitative thematic and conversational analysis were used: themes were co-created and modes of speech and syntactical patterns analysed to expose discourses related to caregiving after placement in 24-hour care homes. Results: Four main themes were co-constructed from the data analysis: living with loss, relinquishing, redefining the caregiving role, and rediscovering and recreating a new self. Discussion: Caregiving continues after placement of family members with dementia in 24-hour care homes. Caregivers are at-risk group and require ongoing support throughout the caregiving journey. Study participants reported that navigation skills such as relationship building, communication, and advocacy were particularly salient to the post-placement period, when navigating the complex health care environment was a significant obstacle. Ultimately, findings from these focus groups will be used to inform an online intervention to support caregivers of a family member with dementia residing in a 24-hour care home.